Identifikasi Harapan Pelanggan terhadap Mutu Pelayanan dan Mutu Proses Produksi Olahan Ikan di CV Mina Utama - Dian Asgar Paradisa; I Wayan Widia; I.G.N. Apriadi Aviantara (Jurnal BETA (Biosistem dan Teknik Pertanian), 2014)
The research aimed to identify (1) the significant of quality service and (2) the quality factor of theproduction processing fish, in according to the expectations of customers in the company CV. Mina Utama.The method used in the research, was asurvey. Results of thisre search showed that the highest level of satisfaction towards quality service factors indicated by the variable of empathy andthe highest level of importance to the factors indicated by the variable of quality service assurance, while the quality factor the aspects of the production processed variable raw materials showed that in terms of the level satisfaction as well in termsof level interest has the highest level.The results were of confirmatory factor analysis showed that, five significant variablesaffecting the quality service thatwas, the variable tangible, reliability, responsiveness,assurance, and empathy, with variable reliabilitybiggest factor in satisfaction and interms of the interestedrate variable responsiveness has the largest factor, the next resultsof confirmatory factor analysis showed that, five significant variables affecting thequality of the production processing that was, the variable raw materials, means of production, production, packaging, and product descriptions, with variable raw materialhas the largestfactor in satisfaction and in terms of the levelvariable interested packaging biggest factor.